2020
DOI: 10.1155/2020/1375741
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Anesthesiologist-Performed Preoperative Echocardiography for the Prediction of Postinduction Hypotension: A Prospective Observational Study

Abstract: Purpose. To determine if left ventricular or inferior vena cava (IVC) measurements are easier to obtain on point-of-care ultrasound by anesthesiologists in preoperative patients, and to assess the relationship between preoperative cardiac dimensions and hypotension with the induction of general anesthesia. Methods. This prospective observational study was conducted at a large academic medical center. Sixty-three patients undergoing noncardiac surgeries under general anesthesia were enrolled. Ultrasound examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Two studies have investigated the relationship between preoperative echocardiography and postinduction hypotension. Szabo et al reported the relationship between IVC and intraoperative hypotension [ 23 ], Fiza et al also conducted a prospective study on preoperative echocardiography and postinduction hypotension [ 24 ], but found no significant association between hypotension and IVC, left ventricular diastolic dimension. They found no significant association between IVC and left ventricular diastolic dimension, possibly due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have investigated the relationship between preoperative echocardiography and postinduction hypotension. Szabo et al reported the relationship between IVC and intraoperative hypotension [ 23 ], Fiza et al also conducted a prospective study on preoperative echocardiography and postinduction hypotension [ 24 ], but found no significant association between hypotension and IVC, left ventricular diastolic dimension. They found no significant association between IVC and left ventricular diastolic dimension, possibly due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of PSH varied from 42.8% [13] to 76% [11] in pregnant patients undergoing caesarean section [11,13] and from 18.3% to 45% in nonpregnant patients [17,18,21]. Incidence of postinduction hypotension varied from 19.3% in the study by Mohammed et al [28] to 70% in the study by Fiza et al [30].…”
Section: Incidence Of Hypotensionmentioning
confidence: 91%
“…Two studies recruited only elderly patients [22,23]. Among the studies done in non-parturient patients, 8 studies excluded American Society of Anaesthesiology (ASA) class ≥ III [15][16][17][18][19][20][21]24], whereas 1 study each included ASA class I-III [25], ASA class II-III [22]and ASA class I-IV [23] Six observational studies evaluated the role of preoperative IVCUS for PIH in non-pregnant patients undergoing elective surgery under GA [26][27][28][29][30][31]. All these studies were done in adult patients.…”
Section: Patient Population and Type Of Surgerymentioning
confidence: 99%
“…Most protocols estimate patients' volume status, and many of them rely on the respiratory variations of the inferior vena cava for this purpose. Although the well-documented methods of preload assessment are less accurate estimates of the uid status or uid responsiveness when used on spontaneously breathing patients [9,10] than in the case of mechanical ventilation [11,12], several studies including our previous experiences identi ed their potential role prior to general anaesthesia [13][14][15][16]. Even though a recent study showed the superiority of variations of left ventricular out ow velocity-time integral (LVOT-VTI) in the prediction of intraoperative hypotension [13], the feasibility of the evaluation of IVC collapsibility index (further IVCCI) still makes it a potential choice to guide perioperative uid therapy.…”
Section: Introductionmentioning
confidence: 99%